PROFIL TOKOH PEREMPUAN DALAM NOVEL METROPOP SUNSHINE BECOMES YOU DAN IN A BLUE MOON KARYA ILANA TAN - Devira, Dhiny; WS, Hasanuddin; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2017)
This research aimed to describe profile of female characters in metropop novel Sunshine Becomes You and In a Blue Moon by Ilana Tan, from basic human attitude of love, beauty, misery, outlook on life, responsibilities, and hopes. DataÂ in this research is a word, phrase, clause, sentence, which can be formulated as profile of female characters. Source of data in this research is metropop novel Sunshine Becomes You and In a Blue Moon by Ilana Tan. This research is a qualitative research and using descriptive analysis method. Based on the result of this research, it can be concluded that basic human attitude wasfound on two female main characters in both novels. Then, after a comparison between the two characters, it can be concluded that the characteristics of the profile of femaleÂ in novels by Ilana Tan has a tendency to fight for the basic attitude of love that is family-oriented and opposite sex. The basic attitude of love family-oriented, including the type of storge love. Meanwhile, the basic attitude of love that is oriented in the opposite sex, including the type of mania love. Furthermore, the profile of female characters in novels by Ilana Tan also has a tendency to fight for basic attitude-oriented outlook on life reflections / thoughts by themselves. outlook on lifeoriented reflections including the type of pragmatism.Keywords: Profile, female,characters, basic human attitude